1999
DOI: 10.1210/jcem.84.10.6041
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Migration as Determinants of Human Prostate Size*

Abstract: The roles of ethnicity and migration in determining the size of human prostate zones during midlife were explored. Prostate size was measured by planimetric ultrasound in 163 men residing in Sydney who were either Australian non-Chinese (AR; n = 116) or Chinese migrants (ACM; n = 47) and had lived in Australia for a median of 7.3 yr (range, 0.2-25 yr). These were compared with Chinese men residing in China (CR; n = 210). Central and total prostate volumes were estimated by a single observer using the same equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
0
17
1
2
Order By: Relevance
“…The third growth period is the pathological enlargement of the prostate, which is the so‐called BPH . The enlargement of the prostate is influenced by age, race, environment, androgens and oestrogens …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third growth period is the pathological enlargement of the prostate, which is the so‐called BPH . The enlargement of the prostate is influenced by age, race, environment, androgens and oestrogens …”
Section: Discussionmentioning
confidence: 99%
“…The size of the prostate varies by country. Studies have found that males in Asia, including China, India and Japan, have lower PV compared with the males in America or Australia . Interestingly, the size of the prostate grows with age.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting outcome of this study is the observation that, despite administration of exogenous testosterone, plasma dihydrotestosterone concentrations are reduced in proportion to reduction in prostate volume and plasma PSA concentrations. This is consistent with the suggestion that most blood plasma dihydrotestosterone arises from the prostate gland where type II 5α reductase is highly expressed and most incoming testosterone is avidly converted to dihydrotestosterone (Gisleskog et al ., 1998; Jin et al ., 1999). Hence in untreated middle‐aged and older men, circulating plasma dihydrotestosterone may be viewed as another convenient indicator of prostate size similar to the interpretation of plasma PSA (Jin et al ., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the suggestion that most blood plasma dihydrotestosterone arises from the prostate gland where type II 5α reductase is highly expressed and most incoming testosterone is avidly converted to dihydrotestosterone (Gisleskog et al ., 1998; Jin et al ., 1999). Hence in untreated middle‐aged and older men, circulating plasma dihydrotestosterone may be viewed as another convenient indicator of prostate size similar to the interpretation of plasma PSA (Jin et al ., 1999). Whether plasma dihydrotestosterone can be viewed as a non‐invasive, quantitative estimate of prostatic type II 5α reductase activity is an interesting and important question requiring further study.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate‐to‐severe LUTS are more prevalent in Asian men than in men in most Western countries 7 . Furthermore, men of Asian ethnicity living in Asia and the Far East have lower PV and PSA levels than Western and Caucasian men, and differences in the relationship between PV and PSA have been reported in populations from China, Taiwan, Korea and Japan 8–10 . Specifically, per volume unit of prostate gland, there might be a greater release of PSA compared with Caucasian men 11 …”
Section: Introductionmentioning
confidence: 99%